THE INFLUENCE OF LOCAL INDONESIAN CULTURE ON METAPHORICAL EXPRESSIONS ON THE REMARK OF THE MINISTER OF FOREIGN AFFAIRS OF THE REPUBLIC OF INDONESIA ON THE CELEBRATION OF THE 55TH ASEAN ANNIVERSARY JAKARTA 8 AUGUST 2022 - Ageng Soeharno; Edhi Siswanto (MEDIAKOM, 2022)
Indonesia is the biggest archipelago country in the world. As the largest archipelagic country in the world, Indonesia has a variety of regional languages, all of which are regional languages ​​that must be developed for its sustainability. In addition to building the preservation of regional languages, the task of preserving not only the Government but also all components of the nation must work hand in hand in preserving it, along with the incessant influx of foreign cultures coming from abroad. because of the world's free trade, especially in ASEAN. The writing of this research theme is considered important because of the importance of language culture in the world of communication, especially in expressing a political statement delivered by a Minister of Foreign Affairs at the level of Minister of Foreign Affairs in the field of state politics. As a country that has influence in its culture and language, Indonesian is also able to influence English, even though the percentage is small, but it is felt necessary that one day Indonesian will become a serious competitor to English in the world, so the author feels the need to review the influence of Indonesian. towards the English language, especially in relation to its metaphorical culture. This study uses a qualitative method. The data used comes from or is obtained through interviews, field notes, personal notes and other official documents.   Keywords: Culture, idiomatic expression, metaphor.